Geodynamics and Nature of the Conrad Boundary by Results of the Deep Electromagnetic Soundings and the Superdeep Drilling - Abdulkhai A. Zhamaletdinov (Global Journal of Earth Science and Engineering, 2018)
Continental Earth’s crust is subdivided into two parts – upper, brittle crust (namely geological) and low, ductile crust (namely physical). This idea has been investigated by many researchers on the base of seismical data, laboratory study of rock specimens at high thermo dynamic conditions and on the base of theoretical speculations [1, 2, 3]. In this presentation this idea is investigated on the base of the deep soundings with powerful controlled sources such as MHD-generator “Khibiny”, industrial power transmitting lines (experiment “FENICS”) and with taking into account results of superdeep drilling on Fennoscandian shield. The summary analysis of the obtained data allows to draw a conclusion that the upper part of continental crystalline earth’s crust has a thickness of the order of 10-12 km. Its principal peculiarities are: the sharp horizontal heterogeneity of electrical properties, a wide range of variations of electrical resistivity from 10 till 104 Ohm∙m, a high porosity, brittleness, and a presence of fluids (meteoric waters) that penetrate from the day time surface to the depths of up to 5-10 km. Upper crust is the most actively involved in geological processes. The low crust belongs to the depth interval from 10–12 to 35–45 km (up to the Moho boundary). It is remarkable by horizontal homogeneity of electrical properties and high electrical resistivity in the range of 105–106 Ohm∙m, by the low porosity and increased ductility. Electrical conductivity of the low crust is mostly determined by influence of planetary physical–chemical parameters (pressure, temperature, and viscosity), phase transitions of substances depending on geodynamic peculiarities of evolution for different segments of the Earth crust. As an area of physical processes influence, the low crust is nearer by its origin to the upper mantle then to the geological Earth crust. The low and upper parts of the Earth crust are subdivided between each other by the boundary of the sharp increase of electrical resistivity at the depth around 10-12 km (so called Boundary of impermeability for DC currents, BIP zone). At the same depth the sharp increase of rocks solidity, viscosity has been met in the Kola superdeep hole. This transition zone between the upper and lower crust is related with hypothetic Conrad boundary predicted by seismic data by the stepwise increase of longitudinal waves from 6 to 6.5 km/s.